Trial by YouTube: effects of expert psychiatric witness testimony on viewers' opinions of Amber Heard and Johnny Depp - Oliver Mason; Beth Horton; Caitlin Starrett (BJPsych Bulletin)
Aims and method We aimed to assess whether viewing expert witness evidence regarding the mental health of Johnny Depp and Amber Heard in the 2022 court case in the USA would affect viewers’ attitudes towards the mental health of the two protagonists and towards mental illness in general. After viewing excerpts of the cross-examination evidence, 38 trial-naive undergraduate students completed the Prejudice towards People with a Mental Illness (PPMI) scale.